Pengembangan Bahan Ajar Bola Tangan Berbasis Video Bagi Mahasiswa STKIP PGRI Lubuklinggau - Azizil Fikri; Popalri Popalri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
This study aims to obtain valid handball teaching materials for Health and Recreation Physical Education students at STKIP PGRI Lubuklinggau. This study uses a Research and Development research and development (R&D) approach, where this research develops teaching material products in the form of a handball game book for students of physical health and recreation education at STKIP PGRI Lubuklinggau. This research is only limited to the development stage at the validation stage. The validity test in this stage is the theoretical validity, namely the validation carried out by experts in their field consisting of three validators. The validation includes language validation, material / content validation and media / design validation. From the results of the handball module research on Health and Recreation Physical Education students developed, it fulfills the validity criteria with language validity values ​​of 94%, media / design validity of 90% and content / material validity values ​​of 94% which can be interpreted as very valid. Conclusion, the handball module for Health and Recreation Physical Education students of STKIP PGRI Lubuklinggau which was developed is very valid. Keywords: Teaching Materials, Handball